CITRA MEREK, BINTANG IKLAN, DAN KESADARAN MEREK: CUKUP KUATKAH DALAM MEMPENGARUHI INTENSI PEMBELIAN KECAP MANIS ABC DI SURABAYA - Rizal Bagus Setiawan; Tatik Suryani (STIE Perbanas Surabaya, 2014)
Customers purchase intention is influenced by many factors. The reason behind why customersbuy is very important for the company to develop its marketing strategy. The purposeof this study is to examine the influence of Brand Image, Celebrity Endorsement, andBrand Awareness on Customers Purchase Intention of ABC Sweet Soy in Surabaya. Thisresearch uses questionnaire as an instrument to get the response of the respondent. A questionnairewas spread to one hundred people who buying and consuming the ABC sweet soyin Surabaya. Multiple Regression Analyze (MRA) is used to examine the effect of the independentvariables on dependent variable. The findings of this study shows celebrity endorsementand brand awareness has positive significant effect on consumers purchase intention,but not to brand image. The implication of this research, the company shouldstrengthen the brand awareness and should be selective to choose celebrity as endorsementon its advertising.